The Effect of Methylprednisolone on Facial Nerve Paralysis With Different Etiologies - Yildirim, Mehmet Akif; Karlidag, Turgut; Akpolat, Nusret; Kaygusuz, Irfan; Keles, Erol; Yalcin, Sinasi; Akyigit, Abdulvahap (Lippincott Williams & Wilkins, 2015)
Objectives: The objective of this study was to evaluate the effectiveness of methylprednisolone (MP) in models of facial nerve paralysis obtained by nerve section, compression, or inoculation with herpes simplex virus (HSV). Study Design: Experimental controlled animal study. Setting: Tertiary referral center. Methods: A total of 30 female New Zealand rabbits weighing 1200-3000 g were used for the study. They were randomly assigned to one of 6 groups of 5 animals each. A nerve section injury was realized in Groups 1a (section and MP) and 1b (section, control) rabbits. A compression-type injury was inflicted to rabbits in Groups 2a (compression and MP) and 2b (compression, control). As for animals in Groups 3a (Type 1 HSV and MP) and 3b (Type 1 HSV, controls), facial nerve paralysis resulting from viral infection was obtained. Animals in the 3 treatment groups, designated with the letter a'', were administered MP, 1mg/kg/d, whereas those in control groups b'' received 1mL normal saline, both during 3 weeks. All subjects were followed up for 2 months. At the end of this period, all animals had the buccal branch of the facial nerve excised on the operated side. Semi-thin sections of these specimens were evaluated under light microscopy for the following: perineural fibrosis, increase in collagen fibers, myelin degeneration, axonal degeneration, Schwann cell proliferation, and edema. Results: No significant difference was observed (P> 0.05) between theMP treatment group and the control group with regard to perineural fibrosis, increase in collagen fibers, myelin degeneration, axonal degeneration, edema, or Schwann cell proliferation. In the group with a compressive lesion (Group 2), controls were no different from MP-treated animals as to perineural fibrosis, increase in collagen fibers, or Schwann cell proliferation, whereas axonal degeneration, myelin degeneration, and edema were significantly higher (P< 0.05) in the control group. When comparing the treatment and control groups among the animals inoculated with Type 1HSV, no significant difference was found with regard to perineural fibrosis, axonal degeneration, myelin degeneration, or Schwann cell proliferation. The only statistically significant advantage of the treatment group was in edema formation (P< 0.05). Conclusions: As a result of the evaluation of MP efficacy in different models of facial nerve palsy, we may say that this drug was without effect on nerve healing in paralysis due to nerve section and that it only reduced nervous edema in paralysis induced by Type 1 HSV, whereas it had positive effects on healing in the type of paralysis caused by nerve compression.
Keywords: Facial nerve palsy; herpes simplex virus Type 1; MP